PENGARUH KUALITAS LAYANAN TERHADAP MOTIVASI DAN LOYALITAS MAHASISWA DENGAN KEPUASAN MAHASISWA SEBAGAI VARIABEL MEDIASI (Studi Pada Poltekkes Kemenkes Banjarmasin) - Muhammad Yamani; Laila Refiana Said; Dahniar (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
This study aims to analyze the effect of service quality on student satisfaction, the influence of service quality on student motivation, the influence of service quality on student loyalty, and analyzing the mediation of student satisfaction on the influence of service quality to student's motivation and loyalty. This research is a quantitative research. This research method used questionnaire with 157 students of Poltekkes Kemenkes Banjarmasin Level II Diploma III program and has been selected from Population 260 students. Measurement of variables using Likert Scale technique. Data analysis used is Structural Equation Modeling (SEM). The result of the research shows that service quality has an effect on student satisfaction, student motivation and student loyalty, but student's satisfaction has no direct effect to student's motivation and loyalty and does not mediate the influence of good service quality to student's motivation and loyalty.